Basic and Clinical Andrology - Mieusset, Roger; Drevet, Joel R.
Basic and Clinical Andrology is an open access journal within the domain of andrology, covering all aspects of male reproductive and sexual health in humans and animal models. The journal aims to bring to light the various clinical advancements and research developments in andrology from the international community.  Basic and Clinical Andrology is a continuation of the French journal Andrologie and is the official journal of the French Society of Andrology (SALF). As an open-access journal, Basic and Clinical Andrology can ensure wide distribution and increased visibility of authors’ work. .